THE CUBAN AND THE UKRAINIAN CRISIS IN ТHE LIGHT OF GLOBAL GEOPOLITICAL DYNAMICS - Stošić, Sanja (Political Review, 2023)
Crises tend to crystallize developments in the world order and although many claim that we live in a postcolonial era, the reality is that the past is not divorced from the present. Even though the Cuban missile crisis in 1962. didn’t end up in raging nuclear warfare, and to a certain degree lessened the Cold War’s tensions by establishing better communication between the White House and the Kremlin, the consequences of the U.S.-Russian strategic confrontation were inherently negative, due to the fact that the Crisis actually served to stimulate an arms race competition between the U.S. and the Soviet Union, and overall, the spread of nuclear weapons. In light of this, the world has become highly unstable. First we had bipolarity, and then, after the Post–Cold War era of relative moderation in international politics, the unipolarity of American hegemony, and now, with China and America as the two main actors, the phase of emerging multipolarity has come. While in the past global peace was kept by preventing major military conflicts between great powers, nowadays, the maintenance of global security and worldwide peace requires not only containment of nuclear proliferation but also the implementation of new nuclear doctrines and policies that will diminish the roll and significance of nuclear weapons, and thus nuclear instability. At the other hand, due to its hegemonic status, the U.S. has started to arrogantly impose its interest all over the world and violate international law. Cultivating the Cold War mentality, while overriding sovereignty and interfering in international affairs of other countries, the U.S. has been using the same recipe for over a 6 decades. Within the scope of dealing with the Cuban and the Ukrainian crisis, the U.S. have used same old strategy and tactics based on subversive regime destabilization – from the imposition of pro-American regimes, unfair and forcefully imposed sanctions, proxy wars, to the creation of false narratives which divide public opinion and incite judgement of other countries, etc. Moreover, under the label of national security, human rights and democracy, since the collapse of the Soviet Union, and against Russian demands, the U.S. continued NATO expansion to the East, endangering Russian security and paving its way to Euroasia. In that sense, the Ukrainian crisis may escalate into Third World War with unpredictable global consequences, or nuclear catastrophe. However, regardless of its final outcome, the Ukrainian crises will fundamentally change the security framework of Europe and the relations between East and West. Actually, the Ukrainian war has only accelerated the change of the geopolitical landscape, which has been going through a deep transformation for a long time. Within the EU, NATO relies on its member countries contributing forces, meaning it may include traditionally neutral countries, as Sweden and Finland. Due to the intensified cooperation between Russia and China, the emerging new world order is being born, and that world order will surely not rely on the American hegemony. The world order with dominant role of the Anglo-Saxons has suffered the dynamic loss and the time of power politics and the balance of power prevails again. In another words, the world is definitely realigning itself, and in its diplomacy, Russia has adapted to global power transition by making associations with different international actors. Overall, the actual Ukrainian crisis has not only brought radical shift in the existing world order and global geopolitical changes, but also a “global energy crisis of unprecedented depth and complexity,” and collapse of today’s Europe. Although for some countries Russia’s invasion of Ukraine was the unexpected scenario of 2022 which has brought problems related to food and energy markets, recent events have shown that both American and the European economy have already been in relative decline. However, the true scope and depth of the Ukrainian crisis’ global impact is only starting to become clear. So, we can conclude that nowadays, we face not only a crisis of enormous dimensions, but a new process of structural change whose end remains unknowable.